Human Rights Protection for Victims of Human Trafficking: A Normative Analysis of Law Number 21 of 2007 - Marcelino Dennis Lesmana; Herry Firmansyah (Al-Risalah, 2026)
Human trafficking constitutes a serious crime that violates human dignity and fundamental human rights. This research analyzes two main issues: (1) the implementation of human trafficking regulations as part of human rights protection in Indonesia; and (2) the categorization of human trafficking within the spectrum of derogable rights or non-derogable rights. The research method employs a normative juridical approach with a statute approach and conceptual approach. Primary data sources include Law No. 21 of 2007 on the Eradication of Human Trafficking, Presidential Regulation No. 69 of 2008 on the Task Force for Prevention and Handling of Human Trafficking, and international human rights legal instruments, while secondary data consist of legal literature, scientific journals, and academic documents related to human trafficking and human rights. Research findings indicate that the implementation of human trafficking regulations has experienced significant development since the enactment of Law No. 21 of 2007, which was strengthened by the establishment of the Task Force through Presidential Regulation No. 69 of 2008 as the coordinator for prevention and handling of human trafficking. Human trafficking falls within the category of non-derogable rights as it violates three fundamental rights that cannot be reduced under any circumstances: the right to life, the right to be free from torture, and the right to be free from slavery. Human trafficking constitutes a serious human rights violation requiring comprehensive legal protection through national regulatory frameworks and commitment to international human rights standards.